2006
DOI: 10.1111/j.1365-2494.2006.00548.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative defoliation tolerance of temperate perennial grasses

Abstract: The defoliation tolerance of cultivars of four temperate perennial pasture grasses, perennial ryegrass (Lolium perenne, cv. Yatsyn1), phalaris (Phalaris aquatica cv. Australian), tall fescue (Festuca arundinaceae cv. Demeter) and cocksfoot (Dactylis glomerata cv. Porto), was determined under controlled conditions over a period of 12 weeks. Undefoliated plants were compared with defoliated plants, where only half of one leaf was left intact at the initial defoliation, and leaf regrowth was harvested every 3-4 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 32 publications
1
24
0
1
Order By: Relevance
“…Indeed, it has been reported that multiple grass defoliations reduced grass root weight, root area, root length, and weight of total nonstructural carbohydrates in roots more than single defoliations did (Engle et al, 1998). Moreover, when defoliation combined with other stresses (low temperatures in this case), enlarged the priority for leaf regrowth at the expense of roots (Fulkerson and Donaghy, 2001;Cullen et al, 2006). It seems that all these factors contributed to a reduced root DM at the end of the first harvest year.…”
Section: Discussionmentioning
confidence: 93%
“…Indeed, it has been reported that multiple grass defoliations reduced grass root weight, root area, root length, and weight of total nonstructural carbohydrates in roots more than single defoliations did (Engle et al, 1998). Moreover, when defoliation combined with other stresses (low temperatures in this case), enlarged the priority for leaf regrowth at the expense of roots (Fulkerson and Donaghy, 2001;Cullen et al, 2006). It seems that all these factors contributed to a reduced root DM at the end of the first harvest year.…”
Section: Discussionmentioning
confidence: 93%
“…This means that following defoliation plants initially replace the removed leaf area and then invest energy into shoot and root growth. in defoliated plants of D. glomerata, low root: shoot ratios (Cullen et al 2005) and an increase in tiller number per plant (Cullen et al 2006) indicate a strong priority for shoot growth and a competitive growth strategy (Grime 1981). Accordingly, D. glomerata can be characterised as a defoliation-tolerant species that has higher regrowth rates than other grass species following defoliation (Cullen et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…in defoliated plants of D. glomerata, low root: shoot ratios (Cullen et al 2005) and an increase in tiller number per plant (Cullen et al 2006) indicate a strong priority for shoot growth and a competitive growth strategy (Grime 1981). Accordingly, D. glomerata can be characterised as a defoliation-tolerant species that has higher regrowth rates than other grass species following defoliation (Cullen et al 2006). Thus the increased DM production under frequent defoliation during the first year could have been attributed to this regrowth habit of D. glomerata.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These act to influence how much the animal eats through metabolic and rumen fill feedback mechanisms, the extent of fibre degradation, protein turnover and greenhouse gas production. Representation of these processes is vital due to their effect on plant defoliation and subsequent regrowth of pasture species (Cullen et al 2006), the effect of plant composition on nutrient return to soils and thus environmental outcomes (Kebreab et al 2002), the prediction of animal performance from plants with different nutrient characteristics (Casler 2001), and the identification of the most suitable supplements for specific pastures (Doyle et al 2005). Nevertheless, thorough testing of mechanistic rumen-feeding decision models are needed to ensure they predict accurately levels of intake, animal performance, ruminal concentrations of nutrients, end products of fermentation, nutrients excreted in urine and faeces, and greenhouse gases emissions.…”
Section: Prehension and Digestion By Animalsmentioning
confidence: 99%